A review on protein extracts from sunflower cake: techno-functional properties and promising modification methods - Gültekin Subaşı, Büşra; Vahapoğlu, Beyza; Capanoglu, Esra; Mohammadifar, Mohammad Amin (Critical reviews in food science and nutrition, 2022)
De-oiled sunflower cake is a sustainable and promising protein source with high phenolic and fiber contents. The cake, which is an industrial by-product has been the subject of many studies investigating various aspects such as protein extraction, functional properties, interaction with other ingredients, and its performance in a wide range of food products. Innovative and conventional techniques of protein extraction from sunflower cake have been investigated to increase extraction yield and improve desired functional characteristics. Modulation of structure of plant-based proteins helps to control their techno-functional properties and widen their applications. Structure modification of proteins by physical methods including ultrasound treatment and gamma irradiation as well as enzymatic and chemical methods has been used to improve the functional properties of sunflower protein. This review collects and critically discusses the available information on techno-functional properties of protein extracts from sunflower cake and how its techno-functional properties can be tailored using various structure modification methods.